Correlation Between Ultrasonographic Response and Anti–Tumor Necrosis Factor Drug Levels in Crohn's disease. Issue 5 (October 2022) - Han, Ze-Min; Elodie, Welera Haissou; Yan, Li-Hua; Xu, Pei-Chun; Zhao, Xin-Mei; Zhi, Fa-Chao
Abstract : Background: Ultrasound is valuable in tight control algorithms for Crohn's disease (CD). However, the correlation between ultrasonographic response and anti–tumor necrosis factor (TNF) drug levels remains unknown. Elucidating this correlation would be helpful in optimizing the use of anti-TNF drugs. Thus, the authors aimed to investigate this correlation. Methods: Between June 2020 and June 2021, all patients with CD who completed anti-TNF induction therapy were retrospectively included. Ultrasound was performed at week 0 and week 14, and proactive therapeutic drug monitoring of anti-TNF drugs was performed at week 14. The receiver operating characteristic (ROC) curve was used in the correlation analysis. Results: Ninety-two patients (60 treated with infliximab and 32 with adalimumab) were included. At week 14, an ultrasonographic response was detected in 43 patients. Patients with ultrasonographic response had significantly higher median drug levels (5.9 mcg/mL for infliximab; 18.2 mcg/mL for adalimumab) than those without (0.9 mcg/mL for infliximab, P < 0.001; 4.8 mcg/mL for adalimumab, P < 0.001). The ROC curve showed a significant correlation between ultrasonographic response and anti-TNF drug levels (area under the curve = 0.79 for infliximab, P < 0.001; area under the curve = 0.86 for adalimumab, P < 0.001). The optimal cut-off values for infliximab and adalimumab correlated with ultrasonographic response were 5.0 and 10.5 mcg/mL, respectively. An incremental increase was observed in ultrasonographic response with higher anti-TNF drug levels. Conclusions: Higher anti-TNF drug levels are associated with an increased likelihood of ultrasonographic response in patients with CD.